Manajemen Strategi Pengembangan Pasar Industri Kripik Jamur Bintang Mas Srengat Kabupaten Blitar - Hendri Budi Santoso; Winarto Winarto (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2024)
Industrial development management must be implemented optimally by business actors, it is an absolute requirement for companies to be able to develop rapidly. The strategies implemented are certainly needed by business actors, starting from utilizing market digitalization, building distribution channels, to providing services that make it easier and satisfy consumers. This research was carried out at a home industry (UMKM) for Bintang Mas Mushroom Chips in Kauman Srengat, Blitar Regency. This research is to find internal and external factors and determine alternative strategies for developing MSMEs in the Bintang Mas mushroom chips industry. The method in this research is a descriptive analysis method. With interviews, documentation and observations at the research location. As a result of the research, several internal factors were found that encouraged the development of the Kauman gold star mushroom chips industry, Srengat District, Blitar Regency. The company has employees who are competent in their fields, utilize digital marketing, fast distribution, and a friendly and good customer service model. Furthermore, external factors include increasing company income, increasing the efficiency and effectiveness of business operations, and adopting various strategies implemented by competitors. Alternative strategies used by the company, namely increasing production capacity and quantity in a continuous improvement framework to meet market demand, expanding cooperative relations between companies and farmers, companies and customers, signifying various promotions, discount strategies for chips mushrooms on certain days, product packaging quality innovation that is more creative and attractive